Programming for reinforced concrete design for two-way restrained solid slab to eurocode 2 - Muhammad Iqbal Hisyam, Mohd Zahari (2015)
In this research, a program is coded by using Microsoft Small Basic in order to carry out the calculations in reinforced concrete design for two-way restrained solid slab as according to Eurocode 2 standards. The aim and objectives of this research is to provide a faster and accurate way to solve reinforced concrete design tests and questions. Other than that, this also seek to provide a free alternative to students or lecturers with minimum system requirements that would work on any Windows operating system as compared to the more advanced yet expensive available software on the market. Coding of the program is done using Microsoft Small Basic, utilizing a simple BASIC programming language, one of the easiest programming to learn and use. Microsoft Small Basic does not require high-end computer specifications including the programs coded through it. Coding is giving instructions to a computer in a language it can understand with the correct syntax. The Program would require certain values to be inputted by the user before proceeding with calculations. Once the program is finished in its coding, its accuracy is then compared to manual calculations of provided questions. This research would act as an aid to users to carry out reinforced concrete design via a free and easy to use software for quick and precise answers.